Refugee Crisis in Jordan: The Logic of Development and Possible Solutions - A. V. Demchenko (Вестник Московского Университета. Серия XXV: Международные отношения и мировая политика)
One major consequence of the conflict in Syria, giving it a truly international dimension, is an unprecedented refugee crisis. The 2015 refugee crisis in the European Union received particularly broad media coverage. However, one should not lose sight of the fact that the largest number of refugees from Syria streamed into neighboring countries, dramatically altering social, economic and political situation there. In this regard the case of the Hashemite Kingdom of Jordan deserves special attention. According to various estimates, Jordan hosted from 600 000 to over 1 300 000 Syrian refugees. At the same time, Jordan’s refugee policy has some peculiarities due to a complex structure of its society and, as a result, the need to maintain an intercommunity balance. The author shows how these circumstances influenced Jordanian legal framework on the issues of migration and asylum. The paper examines the evolution of the Jordan government approaches to the issue of Syrian refugees from 2011, when the country hosted first victims of the conflict, to the present days. In particular, the author emphasizes that if in 2011–2013 refugees could enter the Jordan territory almost without any obstacles, then in 2013–2014 Amman, facing a constantly growing number of refugees, tightened up its asylum policy considerably. However it soon became evident that restrictive measures could not, per se, improve the social and economic situation in the country and have led to criminalization of migrants. As a result, in 2016 the Jordan government took a more flexible stance. On the one hand, Jordan continued to restrict the inflow of refugees but, on the other hand, tried to capitalize on them by seeking additional funding from the United States, the European Union and international organizations in order to mitigate the adverse impacts of the Syrian crisis and to promote its own infrastructural and economic development. However, the author concludes that the prospects for the settlement of the Syrian refugee crisis in Jordan remain unclear. They are wholly dependent on the process of conflict settlement in Syria and should it fail a fragile demographic and political balance in the kingdom will be irretrievably lost.